COMPARATIVE ANALYSIS OF THE KRANJSKA GORA AND ZLATIBOR TOURISM DESTINATIONS’ COMPETITIVENESS IN FUNCTION OF IMPROVING THE TOURISM OFFERCTION TO IMPROVE THE TOURIST OFFER - KRANJSKA GORA AND ZLATIBOR CASE STUDY - Bjelić, Katarina; Vujko, Aleksandra; Panić, Aleksa (The European Journal of Applied Economics, 2024)
The initial hypothesis of the work was the assumption that Zlatibor has potential for tourism development, but that the tourist destination Zlatibor is still not sufficiently competitive with the tourist destination Kranjska Gora. The research presents the key features of these areas, their attractive tourist offer, through a comparative analysis. Also, this paper deals with the chances for the development of sustainable tourism, as well as the improvement of tourist services, specifically Zlatibor, bearing in mind that the Kranjska region is in a much better position, as far as the implementation of the concept of green tourism development. The research was conducted using a modified IMDC model, seeking responses from stakeholders from both Zlatibor and Kranjska Gora (259). Bearing in mind that the responses of stakeholders from Slovenia showed consistently higher values in the assessment of destination competitiveness, the starting hypothesis proved to be correct, and in response to that, guidelines were given for improving competitiveness and overcoming certain threats observed in the research results.